3y
simplify the square foor of 49 times x to the third time y to the sixth times the absolute value of z squared
2x3x-4= -24
you can't because it is not an equation but you can simplify it. The simplified version would be 5x times 9
Log(3 * 1/3) = log(1) = 0
3.001
5 x 3a= 15a
We are multiplying here, so we can combine all of the constants and make that the coefficient for the x. 4 * x * 3 = (4 * 3) * x = 12x.
x cubed, or x³
It means to replace a mathematical expression by a simpler one. For example, if x = 2 times 5 + 3, you can multiply 2 times 5 to obtain x = 10 + 3. Doing the addition will simplify the expression even further.It means to replace a mathematical expression by a simpler one. For example, if x = 2 times 5 + 3, you can multiply 2 times 5 to obtain x = 10 + 3. Doing the addition will simplify the expression even further.It means to replace a mathematical expression by a simpler one. For example, if x = 2 times 5 + 3, you can multiply 2 times 5 to obtain x = 10 + 3. Doing the addition will simplify the expression even further.It means to replace a mathematical expression by a simpler one. For example, if x = 2 times 5 + 3, you can multiply 2 times 5 to obtain x = 10 + 3. Doing the addition will simplify the expression even further.
- - x + 3 = x + 3
x - 2x + 3 = 3 - x
3 * x + 4 + 2xMDAS rule:3x + 4 + 2x5x + 4
-x over 3 can not be simplified.
X = 0.8
3 + x = 8 x = 5
6sqrt(-12)6*2sqrt(-3)12sqrt(3)i12i x sqrt(3)